Pyridinic analog of the natural product (-)-spectaline as potential adjuvant for the treatment of central nervous system disorders - Valli, Marilia [UNESP]; Betti, Andresa Heemann; Danuello, Amanda; Pivatto, Marcos; Centurião, Fernanda; Antonio, Camila Boque; Rates, Stela Maris Kuze; Bolzani, Vanderlan da Silva [UNESP] (Elsevier B.V., 2015)
Previously we designed a series of pyridinic anticholinesterasic compounds based on molecular hybridization between tacrine and the natural piperidine alkaloid (-)-3-O-acetylspectaline isolated from Senna spectabilis. Based on the information that the cholinergic system has an important role in the treatment of schizophrenia and depression, we herein report the evaluation of a series of pyridinic compounds in animal models for antipsychotic and antidepressant-like activities. Compound 2 decreased the immobility time of mice in the forced swimming test (5 and 10 mg/kg p.o.) and prevented the climbing behavior induced by apomorphine (10 mg/kg, p.o.), without impairing animals locomotor activity.
Keywords: Pyridinic alkaloid analogs; Antidepressant-like activity; Antipsychotic; Apomorphine-induced climbing; Forced swimming test